胃すい相関理論概説 - ABE Michio (Japanese Journal of National Medical Services, 1984)
The theory of gastro-pancreatic correlation was outlined.We published a case of Zollinger-Ellison syndrome, probably the seventh in our country as our own case.It was a very valuable case in that we were able to observe it for as long as six years and learn many lessons for elucidating pathophysiology of peptic ulcer.This disease is characterized by formation of intractable ulcer due to gastric juice being secreted endlessly in large quantity beyond the physiological negative feed back mechanism under the stimulus of gastrin produced from pancreatic tumor.We noticed that the contents of frequent vomitus were mostly alkaline and accidentally found the fact that pancreatic secretion was surprisingly excessive, though not equal to the level of gastric secretion.With this fact as an important clue, we assumed that a significant positive correlation would be established between acid secretion and bicarbonate secretion, and after many studies for over many years we were able to find this correlation in normal individuals. The details are mentioned in a separate paper.Many studies on this subject have been done both at home and abroad, particularly abroad, but there seems to be no report that this correlation has been established in normal individuals.When the cause of the failure to establish this correlation was examined, it was mostly related to the problems of a stomach tube for aspiration.The stomach tube should be so designed (1) that the back flow of pancreatic juice into the stomach bee prevented, (2) that pancreatic juice not flow into the inferior small intestine, (3) that gastric juice not flow into the duodenum, making it possible to obtain gastric juice completely isolated from pancreatic juice and (4) that pain to the patients be minimized.As for drugs to be used, the more purified, the better they are. Enough study was made on these problems in the past. So, lenient conditions for estabishing the criteria for the selection of normal controls will have to be pointed out as the remaining problem.From a broad viewpoint of investigating the secretory behavior of the function, we have created a new criterion entirely different from the old one by taking up gastrin and secretin, GI hormones peculiar to the stomach and pancreas and attaching importance to the secretory responses after stimulation related to these hormones, particularly the reserve capacity.The importance of paying attetion to this point is substantiated by the fact that one out of three normal subjects selected according to the old criteria (18/53) showed functional abnormality related to gastrin and secretin.The correlation between acid secretion and bicarbonate secretion mentioned above is clinically very useful.It was made clear that the correlation was concerned with the occurrence and intractability of ulcer as an important factor in case of the relative dominance of acid secretion being observed continuously (Δ acid secretion/Δ bicarbonate secretion (output) ratio ↑) and that it was concerned with chronic diarrhea and intractability in case of the dominance of bicarbonate secretion being observed continuously (Δ acid secretion/Δ bicarbonate secretion (output) ratio ↓).Furthermore, abdominal pain occurred and increased in severity consistent with a rise in the Δacid secretion/Δ bicarbonate secretion (output) ratio and abdominal pain decreased or disappeared with a fall in this ratio. 我が国で始めてZollinger-Ellison症候群が学会でとりあげられ, そのパネル(症例検討)が東大で行われて以来, すでに18年になろうとしている. 演者(3人)の1人として参加した著者は, 当時胃膵相関の手がかりを得たわけで, その後10年間の検討を経てPetersenらが苦慮しているさ中にその成立を見いだすことを可能とした.更に再び9年の歳月が去ろうとしているが, この数年のGIホルモンの進歩はめざましく, GIP (gastric inhibitory polypeptide)をめぐつて胃膵相関の病態解明は核心に迫ろうとしている. GIPは消化性潰瘍, 慢性膵炎で高値を示し, その関与がとくに注目されるところである. 一方, Somatostatinは迷走神経支配下にGIPをブロツクするといわれ, このGIP-Somatostatin系が胃膵臓器相関形成に重要なカギをになつていることが強く示唆される. あるいは更に上位のGRP-GIP-Somatostatin系とその周囲をとり巻く干渉系が今後の大きな臨床課題となつてゆくことであろう.